ISOLATION MICROBE Indigenous TO DEGRADE PROFENOFOS FROM SOIL BEDUGUL AREA - Pradnyana Putra, I Wayan Wisma; Wayan Gunam, Ida Bagus; Anggreni, A.A.M. Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni, 2015)
This study aimed to isolate microbe indiegenous. Samples will takes of soil that has been contaminated by pesticides in Bedugul area. In addition, experiments conduct to determine resistance isolates at high concentrations profenofos. The result of the research showed 6 isolates. Isolates with IPP 02 code, was good growth on Mineral Salt Peptone Yeast medium with 200 ppm concentration profenofos. Keywords : isolation, screening, idiegenous
Keywords: 38